(untitled) (Communications in Computational Physics, 2020)
Massively parallel simulation applied multiple graphic processing units (multi-GPUs) is carried out to perform an in-depth investigation on the flow and heat transfer mechanism in film cooling based on hybrid thermal lattice Boltzmann method (HTLBM). For the flow field, multiple-relaxation-time (MRT) collision model is used. A coolant jet is injected at an inclined angle of α=30◦into a turbulent flat plate boundary layer profile with free-stream Reynolds number of Re = 4000. In our previous work [1], we proposed a three-part definition for the jet-crossflow-interaction region according to the turbulent kinetic energy (TKE) distribution and the unsteady mixing characteristics in each domain were studied qualitatively. In order to further investigate this phenomenon, a more detailed study on unsteady flow and heat transfer characteristics is performed in this work. The results show that the shear domain is dominated by the shearing effect and covered by stable coolant film. In rotating domain, the turbulent intensity increases because of the violent mixing between crossflow and jet flow and the coolant film begins to spread in lateral. All of these cause the rapid decrease in coolant film stability. The great turbulent-dissipation effect in dissipation domain weakens the turbulent intensity and strengthens the fluctuation of spanwise velocity. The cooling performance is very poor.